Road Damage Analysis Using the Analytical Hierarchy Process Method Based on Provincial/District Road Management System as the Basis for Road Handling Program - Zuhri, Fuad Jauhar; Patriadi, Andi; Sajiyo, Sajiyo (Transpublika Publisher, 2025)
This study aims to determine the priority order of road handling in Pacitan Regency using the Analytical Hierarchy Process (AHP) method in combination with the Provincial/District Road Management System (PRMS) application. This research involved provincial roads in Pacitan District, with primary data collection through field surveys and AHP questionnaires distributed to experts. The results of the analysis show that combining the PRMS and AHP methods provides a more accurate and objective prioritization order, with the final result identifying the road sections that need the most urgent handling. prioritization of road handling based on AHP and PRMS methods. Based on the criteria weighting results, the Wareng - Mukus section has the highest priority with a weight of 0.24, followed by the Arjosari - Purwantoro section with a weight of 0.23, and the Bts. Ponorogo Regency - Bts. Pacitan City with a weight of 0.21. In the PRMS analysis, road handling priorities based on TPI (Infrastructure Priority Level) also show similar results, with the Wareng - Mukus section as the highest priority (TPI 33.1), followed by the Bts. Ponorogo Regency - Bts. Pacitan City (TPI 12.2), and the Arjosari - Purwantoro section (TPI 11.2). This research is expected to provide useful recommendations for road management and planning in Pacitan District.